CLINICAL EVALUATION AND MANAGEMENT STRATEGIES FOR PRIMARY OPEN-ANGLE GLAUCOMA - Yusupov Mirza Murodovich (World Scientific Research Journal, 2025)
Annotation: Primary open-angle glaucoma (POAG) is a progressive optic neuropathy characterized by irreversible loss of retinal ganglion cells and visual field defects. It is one of the leading causes of blindness globally, often developing insidiously and remaining asymptomatic until advanced stages. This article investigates the clinical presentation, diagnostic challenges, and therapeutic interventions for POAG through a structured clinical study. The methodology involved comprehensive ocular examinations, intraocular pressure (IOP) monitoring, optical coherence tomography (OCT), and visual field analysis in patients diagnosed with POAG. The analysis emphasizes the correlation between early detection and preserved visual function. Findings highlight the importance of lifelong monitoring and patient-specific treatment regimens, including pharmacologic and surgical options. The study advocates for proactive screening and individualized care plans to prevent vision loss from POAG.